Radical innovations: Between established knowledge and future research opportunities - Victor Tiberius; Hannes Schwarzer; Salvador Roig-Dobón (Journal of Innovation & Knowledge (JIK), 2021)
The fast growing body of radical innovation research is fragmented and difficult to overlook. We provide an overview of the most cited journals, authors, and publications and conduct a bibliographic coupling to structure the literature landscape. We identified the following research clusters: management of radical innovations, organizational learning and knowledge, financial aspects of radical innovation, radical innovation adoption and diffusion, radical industry innovations as challenges for incumbents, and radical innovation in specific industries. Based on an in-depth content analysis of these clusters, we identify the following future research opportunities: A systematic compilation of all intra- and extra-organizational management aspects, moderators, and mediators, extending radical innovation research's epistemological basis by adding strategic foresight, further research in individual, group (team), organizational, and inter-organizational capabilities required for radical innovation, a managerial perspective on adoption and diffusion of radical innovations, applying portfolio theory and real options theory to radical innovation research, stronger research efforts on coping strategies for firms faced with competitors' radical innovations, and intensifying both industry-specific and cross-industry research.
Keywords: D83; O03; 650; Bibliometric analysis; Bibliographic coupling; Citation analysis; Radical innovation